Growth assessment of (002)-oriented AlN thin films on Ti bottom electrode deposited on silicon and kapton substrates. (5th April 2017) - Signore, M.A.; Taurino, A.; Catalano, M.; Kim, M.; Che, Z.; Quaranta, F.; Siciliano, P.
Abstract: In the present work, the sputtering deposition conditions allowing the achievement of (002)-oriented aluminum nitride (AlN) thin films on titanium (Ti) bottom electrode were assessed on both silicon and kapton substrates. The AlN grain orientation was enhanced by tuning the conditions used for the Ti deposition, particularly the radiofrequency (RF) power applied to Ti target and the total pressure in the deposition chamber. Sputtered species energy and their flux towards the substrate were identified as key parameters to interpret Ti structure and morphology on both substrates, and to understand how they drive the AlN crystallization process. The evolution of morphology and structure of single Ti films and of the AlN/Ti system was characterized by X-ray Diffraction, Scanning Electron Microscopy and Transmission Electron Microscopy. Highly oriented AlN films were obtained on both substrates when the underneath Ti layer was mainly (002)-oriented; the presence in the Ti films of grains with (100) orientation produced a degree of misorientation in the following AlN growth, also resulting in a significant change of the surface morphology, on both substrates. The successful deposition of AlN/Ti on kapton substrate represents a promising result for the integration of this material in flexible piezoelectric electronics. Graphical abstract: Highlights: AlN/Ti system was deposited by RF sputtering on Si/SiO2 and kapton substrates for piezoelectric application. Chamber pressure and RF power, were changed during Ti growth to promote (002)-orientation of the overgrown AlN layer. AlN(002) films were successfully obtained on Ti layers, at the highest pressure on kapton substrate and highest power on Si one. The achievement of AlN (002) orientation is particularly important on kapton substrate for piezoelectric flexible electronics.